Unlocking Pathways in Constrained Local Governance: Exploring Paradiplomacy Under Competitive-Disharmony Through the Case of Istanbul - ERTÜRK, AHMET CEMAL; KOUROU, NUR SİNEM (Routledge Journals, Taylor & Francis Ltd., 2024)
Amidst the complexities of globalisation and resurgent global protectionism, paradiplomacy emerges as pivotal in sub-state politics. This paper delves into the case of Turkish local governance post-2019 elections, within a unitary, centralised state structure. Termed 'competitive-disharmony', it scrutinises how opposition mayors in key Turkish metropolitan areas, notably Istanbul, navigate tensions with central authorities through foreign diplomacy. Analysing political activities from 2019 to 2024, the study uncovers strategies used by sub-state actors to assert their interests on the international stage. Focusing on Istanbul, it offers insights into paradiplomacy's role within authoritarian governance structures and evolving city diplomacy. These findings illuminate paradiplomacy's resilience and adaptability, crucial for managing tensions between local and national governments in highly centralised political environments.
Keywords: City Diplomacy; Competitive-Disharmony; Local Governance; Paradiplomacy; Turkish Politics